A Comparison of Learning Achievements in the Subject of Network Configuration in the Lan System according to the Principles of the Network System of the Third-Year Vocational Students Who Learned through Games from the Cisco Aspire Networking Academy Edition Program with Regular Learning Methods - สีหะวงษ์ เกียรติยศ; เสียงล้ำ อาทิตยา; ปัญจพาณิชย์กุล สิทธิชัย; ศักดิ์บุญญารัตน์ ธัญญพัทธ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) compare the learning achievement in the subject of Network Configuration in LAN system based on network system principles between the students who receive learning management using games from the Cisco Aspire Networking Academy Edition program and the students who learned with the regular learning management, and 2) examine students’ satisfaction with game-based learning from the Cisco Aspire Networking Academy Edition program. The sample group consisted of third-year vocational certificate students at Eastern Technological College (E-Tech), selected using cluster random sampling. They were divided into two groups: an experimental group and a control group, each consisting of one classroom with 49 students, for a total of 98 students. The research instruments included game-based learning management plans, regular learning management plans, learning achievement tests, and satisfaction questionnaires. Data were analyzed by using mean, standard deviation, and independent t-test. The research findings indicated that 1) the students who received learning management using games from the Cisco Aspire Networking Academy Edition program had higher academic achievement than the students who received regular learning management, with statistical significance at the .05 level, and 2) students’ overall satisfaction with game-based learning management from the Cisco Aspire Networking Academy Edition program was at a high level. (Mean = 4.22, S.D. = 0.73)